The Dawn of Dutch. Language contact in the Western Low Countries before 1200 - Michiel de Vaan (John Benjamins Publishing Company, 2017)
The Low Countries are famous for their radically changing landscape over the last 1,000 years. Like the landscape, the linguistic situation has also undergone major changes. In Holland, an early form of Frisian was spoken until, very roughly, 1100, and in parts of North Holland it disappeared even later. The hunt for traces of Frisian or Ingvaeonic in the dialects of the western Low Countries has been going on for around 150 years, but a synthesis of the available evidence has never appeared. The main aim of this book is to fill that gap. It follows the lead of many recent studies on the nature and effects of language contact situations in the past. The topic is approached from two different angles: Dutch dialectology, in all its geographic and diachronic variation, and comparative Germanic linguistics. In the end, the minute details and the bigger picture merge into one possible account of the early and high medieval processes that determined the make-up of western Dutch.
English
Keywords: Germanic languages; Historical linguistics; Dutch